The Impact of Brand Awareness and Trust on Purchase Decisions: A Case Study of AQUA in Indonesia - Freesia, Hanifa Ismi (Journal of Business, Management, and Social Studies, 2024)
Objective – To determine the influence of brand awareness and brand trust on the purchase decisions of AQUA brand bottled mineral water at The FoodHall, Grand Indonesia Mall, particularly in light of the controversy surrounding BPA content in AQUA’s packaging.Methodology – This study utilizes a quantitative approach, employing a purposive sampling of 100 consumers at The FoodHall Grand Indonesia Mall, who completed online questionnaires, and analyzes the collected data using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0 to determine the relationships between brand awareness, brand trust, and purchase decisions.Findings – The study found that both brand awareness and brand trust have a statistically significant positive effect on purchasing decisions for AQUA bottled water at The FoodHall Grand Indonesia Mall, indicating that consumers are more likely to buy AQUA when they recognize and trust the brand. Brand trust has the most influence on purchasing decisions.Novelty – The study examines brand awareness and brand trust in the specific context of the recent BPA controversy surrounding AQUA. This provides a timely and relevant analysis of how a brand’s reputation is affected by product safety concerns. Although brand awareness and trust have been evaluated in past research, the direct relationships examined in this study have not yet been previously investigated using a sample of AQUA consumers at The FoodHall Grand Indonesia Mall.